A new synonym and a new combination in Stipa aliena Keng (Poaceae: Stipa sect. Regelia) - Nobis, Marcin; Nowak, Arkadiusz; Gudkova, Polina D (Phytotaxa, 2015)
Stipa section Regelia comprises three species occurring in mountainous areas of Central Asia. One of them, S. smithii, was described by Martinovský in 1970, but the taxon has been overlooked in later taxonomical studies. The species was described with two varieties, var. smithii and var. macrocarpa. As a result of our taxonomical studies, we find the typical variety of the taxon to be conspecific with Stipa aliena, and propose that the second one be recognized as Stipa aliena var. macrocarpa comb. nov. Remarks on species belonging to section Regelia and micromorphological patterns of their lemma morphologies are discussed. A key to species close to S. aliena is provided.